Examining The Effect Of Managerial Competency, Change Management Practices And Communication Skills On Customer Satisfaction at Blimbing Manis Listrik - Unedo Hence Markus; Stefan Kwentino; Syahrilla Sintha; Ramadhina Diffa Walia Saputri; Innocentius Bernarto (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to examine the influence of managerial competency, change management practices, and communication skills on customer satisfaction at Blimbing Manis Listrik. This study used a quantitative, survey-based approach, involving 219 respondents as the research sample. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to simultaneously and comprehensively test the causal relationships among variables. The analysis indicates that communication skills have the greatest influence on customer satisfaction, followed by managerial competency, which also contributes positively and significantly. Meanwhile, change management practices exert a smaller but still significant influence on customer perceptions of the company's services. These findings indicate that management's ability to communicate effectively, clearly, and responsively plays a key role in building trust and increasing customer satisfaction levels. In practice, this study provides strategic implications for Blimbing Manis Listrik management to focus on developing communication and managerial competencies to improve service quality and organizational competitiveness